Correlation between dermoscopic and histopathological findings of leucoplakia of the tongue: a case report. Issue 8 (October 2018) - Okamoto, T.; Tanaka, M.; Kaibuchi, N.; Kuwazawa, T.; Ando, T.
Abstract: A 75-year-old Japanese man presented at our outpatient clinic with pain on the right side of his tongue. Comparison of histological and dermoscopic images showed that areas with hyperkeratosis were opaque white, areas above the papillary dermis were reddish, and that the lesion looked whiter on dermoscopy the longer the epithelial rete ridges were. A dermatocope shows structural information from the epidermis as well as the upper dermis, and could improve early diagnosis of oral mucosal squamous carcinoma in situ.